2011
DOI: 10.1176/appi.ajp.2010.10060792
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of National Health Care Reform on Adults With Severe Mental Disorders

Abstract: Public insurance programs that currently play a major role in financing mental health services will play an even greater role after reform is implemented. Significant increases can be expected both in the overall number of users of mental health services and in their resources to pay for care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(102 citation statements)
references
References 34 publications
(27 reference statements)
3
99
0
Order By: Relevance
“…Compared to participants with no usual provider, patients with evidence of psychological need who reported having a PCMH were more likely to visit a mental health specialist and receive mental health counseling treatment during a subsequent 12-month period. The importance of these findings is heightened by the ACA insurance expansions 13 and states' adoption of PCMH reforms ,17 which are expected to significantly increase the number of adults with mental disorders who will have access to PCMH providers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to participants with no usual provider, patients with evidence of psychological need who reported having a PCMH were more likely to visit a mental health specialist and receive mental health counseling treatment during a subsequent 12-month period. The importance of these findings is heightened by the ACA insurance expansions 13 and states' adoption of PCMH reforms ,17 which are expected to significantly increase the number of adults with mental disorders who will have access to PCMH providers.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Consequently, mental health disorders are often associated with disruptions in relationships, education, and employment, as well as lost productivity, poor health outcomes, increased risk of suicide, and premature mortality. [6][7][8][9][10][11][12] Primary care is often the first place for treatment of mental disorders, 13 and this is expected to increase with promulgation of the integrated care approach established by the Affordable Care Act (ACA). 14 Primary care providers (PCPs) are increasingly charged with screening, diagnosing, treating, and referring patients for treatment of mental health disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Need factors, such as having a diagnosed mental disorder or suffering from more severe mental health problems, have indeed been identified as the most important predictors of utilization in different countries (e.g., Burns et al 2003;Leaf et al 1988;Parslow and Jorm 2000;Schomerus et al 2012). However, predisposing and enabling factors -such as female gender (Angst et al 2005;Bijl et al 2003;Bovier et al 2001;Burgess et al 2009;Fleury et al 2014;Wang et al 2007), higher educational level (Bijl and Ravelli 2000;Kovess-Masfety et al 2007;Parslow and Jorm 2000;Schomerus et al 2012;Wang et al 2007), more positive attitudes towards help-seeking (ten Have et al 2010) and having health insurance (e.g., Garfield et al 2011) -have repeatedly been shown to increase the likelihood of using mental health services even after adjusting for need.…”
Section: Introductionmentioning
confidence: 99%
“…Less severe yet still chronic mental illnesses contribute to absenteeism and loss of employment [33]. As a consequence, people living with mental illness are far more likely to be uninsured or marginally insured than healthy or physically ill individuals [34], likely contributing to the observation that three quarters of premature mortality of individuals with mental illness are attributable to other health conditions that are often treatable [35].…”
Section: Factors Associated With Premature Mortality In People With Mmentioning
confidence: 99%